Synthesis, Structure-Activity Relationships and In Vitro Toxicity Profile of Lactose-Based Fatty Acid Monoesters as Possible Drug Permeability Enhancers - Simone Lucarini; Laura Fagioli; Robert Cavanagh; Wanling Liang; Diego Romano Perinelli; Mario Campana; Snjezana Stolnik; Jenny K. W. Lam; Luca Casettari; Andrea Duranti (MDPI AG, 2018)
Permeability enhancers are receiving increased attention arising from their ability to increase transepithelial permeability and thus, bioavailability of orally or pulmonary administered biopharmaceutics. Here we present the synthesis and the in vitro assaying of a series of lactose-based non-ionic surfactants, highlighting the relationship between their structure and biological effect. Using tensiometric measurements the critical micelle concentrations (CMCs) of the surfactants were determined and demonstrate that increasing hydrophobic chain length reduces surfactant CMC. In vitro testing on Caco-2 intestinal and Calu-3 airway epithelia revealed that cytotoxicity, assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and lactate dehydrogenase (LDH) release assays, is presented for most of the surfactants at concentrations greater than their CMCs. Further biological study demonstrates that application of cytotoxic concentrations of the surfactants is associated with depolarizing mitochondrial membrane potential, increasing nuclear membrane permeability and activation of effector caspases. It is, therefore, proposed that when applied at cytotoxic levels, the surfactants are inducing apoptosis in both cell lines tested. Importantly, through the culture of epithelial monolayers on Transwell® supports, the surfactants demonstrate the ability to reversibly modulate transepithelial electrical resistance (TEER), and thus open tight junctions, at non-toxic concentrations, emphasizing their potential application as safe permeability enhancers in vivo.